(untitled) (Global Journal of Science Frontier Research, 2020)
In private life frequently appears need the guarantee of individual water supply on the place of residence or on the dacha. For these purposes are used the water-bearing bore holes, which are carried out with the aid of the drilling rigs. This is the expensive operation, since it requires not only the presence of drilling rig, but also requires installation in the bore hole of the well casings of large diameter. The large diameter of pipes is caused by the need for the installation in them of immersion water pumps. In the article several versions of the use of water ejector pumps for the solution of this problem are proposed.